VD_FINDINFO Jug / 2024 / 122 vom 1. Januar 2021 - VD Tribunal cantonal (2021)
CORRUPTION, CORRUPTION ACTIVE, CORRUPTION PASSIVE, ESCROQUERIE, SOLIDARITÉ, INDEMNITÉEN GÉNÉRAL | 146 CP, 158 ch. 1 al. 3 CP, 305bis CP, 322novies CP, 322octies CP, 34 CP, 40 CP, 42 al. 1 CP, 71 al. 1 CP, 71 al. 3 CP, 73 CP